L’influence de la technique de pose sur l’adaptation marginale du MTA : étude comparative in vitro - ABLA, Diana; NAAMAN, Alfred (International Arab Journal of Dentistry (IAJD), 2011)
Teeth with open apices require a particular approach, which is to create an apical barrier and to hermetically seal large foramina. The objective of this study was to compare, in vitro, the apical seal obtained with MTA after its introduction into the canal with two different techniques. For this purpose, 102 maxillary and mandibular extracted teeth were selected. Root canals were shaped and randomly divided into two groups (n = 50 per group). The last five millimeters (mm) were filled with white MTA by two different techniques: MTA powder mixed with distilled water and MTA powder and distilled water introduced separately. The two “negative control” teeth (1 tooth in each group) were covered with two layers of varnish, including the apical foramen. The last 6 mm of all samples were immersed in 2% methylene blue dye for 7 days. The dye-penetration was detected by performing horizontal cuts that have been examined with a light microscope (×20). Statistical analysis performed with independent t-test and Fisher exact test showed a significant difference between the two techniques.